Conversion of Partially Reprogrammed Cells to Fully Pluripotent Stem Cells Is Associated with Further Activation of Stem Cell Maintenance- and Gamete Generation-Related Genes - Kim, Jong Soo (Mary Ann Liebert, Inc., 2014)
Somatic cells are reprogrammed to induced pluripotent stem cells (iPSCs) by overexpression of a combination of defined transcription factors. We generated iPSCs from mouse embryonic fibroblasts (with Oct4-GFP reporter) by transfection of pCX-OSK-2A (Oct4, Sox2, and Klf4) and pCX-cMyc vectors. We could generate partially reprogrammed cells (XiPS-7), which maintained more than 20 passages in a partially reprogrammed state; the cells expressed Nanog but were Oct4-GFP negative. When the cells were transferred to serum-free medium (with serum replacement and basic fibroblast growth factor), the XiPS-7 cells converted to Oct4-GFP-positive iPSCs (XiPS-7c, fully reprogrammed cells) with ESC-like properties. During the conversion of XiPS-7 to XiPS-7c, we found several clusters of slowly reprogrammed genes, which were activated at later stages of reprogramming. Our results suggest that partial reprogrammed cells can be induced to full reprogramming status by serum-free medium, in which stem cell maintenance- and gamete generation-related genes were upregulated. These long-term expandable partially reprogrammed cells can be used to verify the mechanism of reprogramming.